2007
DOI: 10.1101/lm.581907
|View full text |Cite
|
Sign up to set email alerts
|

GAP-43 gene expression regulates information storage

Abstract: Previous reports have shown that overexpression of the growth-and plasticity-associated protein GAP-43 improves memory. However, the relation between the levels of this protein to memory enhancement remains unknown. Here, we studied this issue in transgenic mice (G-Phos) overexpressing native, chick GAP-43. These G-Phos mice could be divided at the behavioral level into "spatial bright" and "spatial dull" groups based on their performance on two hidden platform water maze tasks. G-Phos dull mice showed both ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 60 publications
3
27
0
Order By: Relevance
“…The changes in behavior of our HuD OE mice appeared to be different from GAP-43 OE mice, which show increased learning of a delayed non-matching to sample task . Interestingly, a recent study suggests that not all of the GAP-43 OE mice have increased learning abilities and animals that have excessive amounts of GAP-43 in the hippocampus show substantial learning and memory deficits (Holahan et al, 2007). It will therefore be of interest to determine whether the levels of GAP-43 considered excessive in that report are close to those generated in the present study.…”
Section: Discussionsupporting
confidence: 39%
“…The changes in behavior of our HuD OE mice appeared to be different from GAP-43 OE mice, which show increased learning of a delayed non-matching to sample task . Interestingly, a recent study suggests that not all of the GAP-43 OE mice have increased learning abilities and animals that have excessive amounts of GAP-43 in the hippocampus show substantial learning and memory deficits (Holahan et al, 2007). It will therefore be of interest to determine whether the levels of GAP-43 considered excessive in that report are close to those generated in the present study.…”
Section: Discussionsupporting
confidence: 39%
“…Correlation analysis showed that the increased hippocampal levels of GAP-43 induced by catalpol treatment was associated with spatial memory performance, those rats with higher hippocampal GAP-43 expression required less trial times to reach learning criterion, and they showed more correct response to avoid foot shocks in the retention experiment. Studies by others have suggested the amount of GAP-43 in the hippocampus is significantly correlated with performance in the memory task [3,28], and they are consistent with our findings. We can draw a conclusion that catalpol may increase memory by up-regulating GAP-43 level in the hippocampus of aged dementia rats.…”
Section: Increased Hippocampal Levels Of Gap-43 Are Correlated With Ssupporting
confidence: 93%
“…In the third task used, the Morris water maze (for methods, see Holahan et al, 2007), differential performance among the 3 transgenic lines was also revealed. Here the G-NonP mice (n = 6) distinguished themselves by their poor retention performance on the probe test relative to the other groups (Fig 1C and D).…”
mentioning
confidence: 99%